2008
DOI: 10.1111/j.1365-2982.2007.01039.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of autonomic dysfunction in patients with irritable bowel syndrome using fingertip blood flow

Abstract: Fingertip blood flow (FTBF) as measured by laser Doppler flowmetry (LDF) measurement is considered an indicator of sympathetic nerve function. We evaluated autonomic function in patients with irritable bowel syndrome (IBS) by assessing FTBF with both LDF and continuous-wave (cw) Doppler sonography. Firstly, the two methods were compared in 40 healthy volunteers. Next, 59 patients with IBS as well as 118 healthy volunteer controls were studied. In the supine position, FTBF in the right index finger was measured… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
1
2

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 31 publications
(41 reference statements)
3
15
1
2
Order By: Relevance
“…As might be expected, increased sympathetic nervous system activity and decreased parasympathetic nervous system activity were the most frequently noted differences when IBS patients were compared with healthy controls (Table 1). Recently we reported on autonomic nervous system dysfunction in patients with IBS using fingertip blood flow as measured by laser Doppler flowmetry (Tanaka et al, 2007). We found that IBS patients had increased sympathetic nervous system activity, which is consistent with previous studies.…”
Section: Autonomic Nervous System Function In Ibs Patientssupporting
confidence: 91%
See 2 more Smart Citations
“…As might be expected, increased sympathetic nervous system activity and decreased parasympathetic nervous system activity were the most frequently noted differences when IBS patients were compared with healthy controls (Table 1). Recently we reported on autonomic nervous system dysfunction in patients with IBS using fingertip blood flow as measured by laser Doppler flowmetry (Tanaka et al, 2007). We found that IBS patients had increased sympathetic nervous system activity, which is consistent with previous studies.…”
Section: Autonomic Nervous System Function In Ibs Patientssupporting
confidence: 91%
“…Tillish et al (2005) reported the same results as Robert et al (2006). Our data (Tanaka et al, 2007) were also consistent with these reports. Data from previous studies has been inconsistent regarding bowel habit effect, with the complicating factors being difficulties in classification and possible multiple physiological pathways for a similar symptom picture.…”
Section: Differences In Autonomic Function Among Ibs Symptom Subgroupssupporting
confidence: 91%
See 1 more Smart Citation
“…In recent years, laser Doppler flowmetry-noninvasive continuous measurement of BF-has been applied extensively to study various tissues including fingertip skin (Khan et al, 1992;Littleford et al, 1999;Abbink et al, 2001;Mayrovitz and Groseclose, 2002;Freccero et al, 2003;O'Brien, 2005;Tanaka et al, 2008;Hayashi et al, 2009). However, simultaneous measurement of BF and StO 2 in a small area of human fingertip skin has not been reported.…”
Section: Introductionmentioning
confidence: 98%
“…[9] The autonomic nervous system as well as stress hormone system and psychoneuroimmunological branches of the brain-gut axis may be mediators of this link. [10][11][12] Psychosomatic research was shown to link the predisposition to functional gastrointestinal illness with specific personality states and the onset of symptom with exposure to stressful life events. [13] Alexithymia is considered to be a personality state of deficiency in understanding, processing, or describing emotions.…”
Section: Introductionmentioning
confidence: 99%